Chinese Immigrant Women's Perspectives on Communication Strategies of Healthcare Providers During Gynecological Examinations - Lu, Yutong (Université d'Ottawa / University of Ottawa, 2026)
Effective and appropriate communication is a key component of positive clinical experience, while immigrant women's experiences during intimate medical encounters remain underexplored. This thesis explores how Chinese immigrant women perceive, interpret, and engage in communication with healthcare providers during gynecological examinations in Canada. Drawing on Communication Accommodation Theory and patient‑centred communication, the study investigates how patients' emotional experiences, sense of agency, and perceptions of care quality are influenced by the communication strategies encountered. Using a qualitative research design, in‑depth semi‑structured interviews were conducted with twelve Chinese immigrant women who lived in Canada. Data were analyzed following Braun and Clarke's (2006) six-step thematic approach. The results were presented in three major themes: Communication Accommodation Strategies in Addressing Language Barriers; Patient-centred Communication in Alleviating Stress; and Cultural Beliefs Shaping Perceptions of Gynecological Care. Findings indicate that communication during gynecological examinations was co‑constructed through healthcare providers' strategies, patients' cultural backgrounds, and patients' active agency. Participants valued provider‑initiated accommodations and patient‑centred practices, such as linguistic adjustment, anticipatory explanations, privacy protection, and emotional reassurance, which helped reduce anxiety and foster trust. Importantly, patients were not passive recipients of care but actively prepared for and navigated examinations through information‑seeking, familiarisation with medical terminology, and in‑encounter questioning. Patient agency emerged as a significant theme shaping how communication strategies were interpreted and negotiated by participants. While cultural beliefs related to sexuality and hierarchy influenced expectations, their impact varied by length of residence, education, and health literacy, highlighting communication as a dynamic and relational process rather than a unidirectional provider‑led intervention. This thesis contributes to scholarship on healthcare communication by foregrounding immigrant women's voices in gynecological care and demonstrating how accommodation and patient‑centred practices intersect in intimate clinical contexts. The findings offer practical implications for improving communication training and promoting more humane, respectful, and empowering care for diverse patient populations.
Keywords: Immigrant Healthcare Experience; Patient-centred Communication; Communication Accomodation Theory